Physical- and Cognitive-Effort-Based Decision-Making in Depression: Relationships to Symptoms and Functioning. (January 2021) - Tran, Tanya; Hagen, Amanda E. F.; Hollenstein, Tom; Bowie, Christopher R.
Major depressive disorder (MDD) is associated with persistent, impaired life functioning. Motivational deficits in physical and cognitive effort expenditure have not been evaluated as contributors to functional impairment in MDD. In this study, we adapted parallel measures of choices to expend physical and cognitive effort and assessed their associations with symptoms, cognition, and life functioning in 44 participants with MDD. Higher anhedonia severity predicted lower motivation for physical effort but not for cognitive effort. Lower cognitive effort motivation was associated with poorer life functioning even after controlling for previously established predictors of symptoms and cognitive impairment. Reduced cognitive effort motivation also had an indirect effect on the relationship between impaired cognitive and life functioning. Findings suggest motivational deficits in MDD present different barriers for recovery depending on the type of effort that is avoided. Physical effort motivation is associated with anhedonia severity, whereas cognitive effort motivation is relevant to life functioning.